Cognate objects of weather verbs in African languages of South Africa –from synchronic variation to a grammaticalization path - Andrason, Alexander; Visser, Marianna W. (Stellenbosch Papers in Linguistics, 2017)
The authors argue that the synchronic variation of cognate objects of weather verbs exhibited in six African languages of South Africa (Sepedi, Sesotho, Tshivenda, isiXhosa, Xitsonga, and isiZulu) has a diachronic explanation, and may be represented as a grammaticalization path. This path gradually leads from prototypical cognate objects that disallow object agreement (pronominalization) and promotion to subjects in passive constructions to prototypical objects where both agreement (pronominalization) and promotion are grammatical. This provides further support for the modelling of cognate objects, adjuncts and arguments in terms of a continuum and for a gradient view of syntactic categories, in general.